IMPLEMENTATION OF EUROPEAN STANDARDS FOR OCCUPATIONAL SAFETY AND HEALTH IN UKRAINE - Protasenko, O.; Mykhailova, Ye. (Municipal economy of cities. Series: «Economy science», 2024)
The article analyses the European legislation for occupational safety and health, considers the ways of its implementation in the Ukrainian legislation, and studies the available results of bringing the Ukrainian and EU legislation in line. It establishes the necessity to ensure the efficient cooperation of the labour organisation system structures and the continuous interaction of employers with workers to improve the effectiveness of European standards.